Pendidikan Karakter Siswa Kelas IV melalui Pembelajaran Bahasa Indonesia di SDN 19 Meulaboh - Murni, Intan Permata (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
The Value of Character Education in Indonesian Language Learning for Fourth Grade Students at SD N 19 Meulaboh. This study aims to determine the value of character education contained in the Indonesian language learning process for fourth grade students at SD N 19 Meulaboh. This research includes field research. The approach used is descriptive qualitative, data collection techniques using the method of observation and documentation. The focus of this research is the value of character education contained in learning Indonesian in fourth grade students at SD N 19 Meulaboh. The results showed that the planning made by the teacher consisted of initial activities, core activities, and closing activities. The implementation of character education at SD N 19 Meulaboh has not been maximized. The results of the study show that the 18 character values ​​found in learning Indonesian for class IV are religious, honest, tolerance, disciplined, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative, love peace, love to read., care for the environment, responsibility, and care about social.